The professional practice of Jungian coaching : corporate analytical psychology - O'Brien, Nada; O'Brien, John (London : Routledge, 2020)
O'Brien and O'Brien and their collection of international contributors introduce the historical and current theory and practice of Corporate Analytical Psychology. Uniquely and practically bringing Jungian ideas to the corporate world, the chapters discuss the increasing need for ethical corporations in the context of individuation and moral hazard, demonstrate how to manage and define complexes that inhibit creativity and productivity, and shows practitioners how to recognise and connect with symbols as an active and living manifestation of the personal and collective psyche. The book is illustrated with practical examples and case studies encountered by the authors during their 30 years of experience consulting the world's leading companies and institutions.
OCLC-licensed vendor bibliographic record.
Keywords: Psychology, Industrial; Corporate culture -- Psychological aspects; Jungian psychology; PSYCHOLOGY / Industrial & Organizational Psychology; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Movements / Jungian